3D LASER SCANNING AND DIGITAL MAPPING TECHNOLOGIES FOR OPTIMIZED LARGE BLOCK EXTRACTION IN MARBLE QUARRIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The integration of three-dimensional (3D) laser scanning and digital point cloud processing into marble quarry operations represents a paradigm shift in block extraction planning and quality control. This study evaluates the implementation of terrestrial laser scanning (TLS) systems across quarry sites in Uzbekistan, Italy, Turkey, and Greece, assessing improvements in block volume accuracy, fracture detection, and rejection rate reduction. Results demonstrate that 3D scanning technology achieves block volume accuracy improvements of 93.3%, reduces block rejection rates from 22.4% to 4.1%, and decreases fracture detection failure rates by 59%. The adoption trajectory in Uzbekistan's nascent marble sector is analyzed, with pilot program data from the Nurata region confirming an estimated ROI period of 24 months — competitive with the 14–21-month range reported in established European quarrying nations.